Impact of overlapping newer generation drug-eluting stents on clinical and angiographic outcomes: pooled analysis of five trials from the international Global RESOLUTE Program. Issue 9 (6th March 2013) - Farooq, Vasim; Vranckx, Pascal; Mauri, Laura; Cutlip, Donald E; Belardi, Jorge; Silber, Sigmund; Widimsky, Petr; Leon, Martin; Windecker, Stephan; Meredith, Ian; Negoita, Manuela; van Leeuwen, Frank; et al.
Abstract : Background: Overlapping first generation sirolimus- and paclitaxel-eluting stents are associated with persistent inflammation, fibrin deposition and delayed endothelialisation in preclinical models, and adverse angiographic and clinical outcomes—including death and myocardial infarction (MI)—in clinical studies. Objectives: To establish as to whether there are any safety concerns with newer generation drug-eluting stents (DES). Design: Propensity score adjustment of baseline anatomical and clinical characteristics were used to compare clinical outcomes (Kaplan–Meier estimates) between patients implanted with overlapping DES (Resolute zotarolimus-eluting stent (R-ZES) or R-ZES/other DES) against no overlapping DES. Additionally, angiographic outcomes for overlapping R-ZES and everolimus-eluting stents were evaluated in the randomised RESOLUTE All-Comers Trial. Setting: Patient level data from five controlled studies of the RESOLUTE Global Clinical Program evaluating the R-ZES were pooled. Enrolment criteria were generally unrestrictive. Patients: 5130 patients. Main outcome measures: 2-year clinical outcomes and 13-month angiographic outcomes. Results: 644 of 5130 patients (12.6%) in the RESOLUTE Global Clinical Program underwent overlapping DES implantation. Implantation of overlapping DES was associated with an increased frequency of MI and more complex/calcified lesion types at baseline. Adjusted in-hospital, 30-day and 2-year clinical outcomes indicated comparable cardiac death (2-year overlap vs non-overlap: 3.0% vs 2.1%, p=0.36), major adverse cardiac events (13.3% vs 10.7%, p=0.19), target-vessel MI (3.9% vs 3.4%, p=0.40), clinically driven target vessel revascularisation (7.7% vs 6.5%, p=0.32), and definite/probable stent thrombosis (1.4% vs 0.9%, p=0.28). 13-month adjusted angiographic outcomes were comparable between overlapping and non-overlapping DES. Conclusions: Overlapping newer generation DES are safe and effective, with comparable angiographic and clinical outcomes—including repeat revascularisation—to non-overlapping DES. ClinicalTrials.gov Identifiers: NCT00248079; NCT00617084 ; NCT00726453 ; NCT00752128 ; NCT00927940 .